Gerakan Perilaku Sadar Lingkungan melalui Pengelolaan Sampah Domestik dalam Mendukung Green Village Berkelanjutan - Hendy Setiawan; Sufrotun Khasanah; Choirunnisa Choirunnisa (Pakis Journal Institute, 2026)
The waste issue in Batang Regency is still a serious problem that has not been resolved to this day. The problem is that the availability of final waste disposal sites is not comparable to the waste production produced. Therefore, this situation creates an imbalance where the increasing waste production is not accompanied by an adequate expansion of waste disposal areas. Most of the waste in Batang Regency comes from household waste. Therefore, in response to this reality, the most possible thing to do is to carry out household-based awareness control. The community service method used in this paper uses a household waste management education model through the village government. Meanwhile, the village targeted for this community service is Karanganom Village, where coincidentally at the time the community service was being held, a Real Work Lecture was being held. This community service involved components of the community service team starting from a team of lecturers who collaborated with students participating in the Real Work Lecture. The results of the community service show that the Karanganom Village Government agrees that the community must have knowledge of household waste management. Their existence is the first step to controlling waste. Public enthusiasm increased when several places were provided with garbage disposal bin facilities so that they were able to select and sort the garbage that had to be managed and that which had to be thrown in the trash.